2021
DOI: 10.1007/s40122-021-00237-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Methylnaltrexone for the Treatment of Opioid-Induced Constipation: A Meta-analysis of Randomized Controlled Trials

Abstract: Introduction: Opioid-induced constipation (OIC) is a distressing side effect during opioid analgesia and is mainly mediated by gastrointestinal l-opioid receptors. Methylnaltrexone, a peripheral l-opioid receptor antagonist with restricted ability to cross the blood-brain barrier, may alleviate OIC without reversing analgesia. We performed a meta-analysis to assess the efficacy and safety of methylnaltrexone for the treatment of OIC. Methods: This meta-analysis was registered in PROSPERO (CRD42020187290). We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The implementation of the bowel regimen protocol also resulted in a significant increase in the number of BMs for patients in the intervention group, in contrast to the comparison group. This finding is consistent with previous studies that have shown the effectiveness of bowel regimens in improving bowel function (Mozaffari et al, 2018; Zhang et al, 2021). The dynamic role of the case manager in the medical oncology unit helped the nursing and medical teams determine the BM status of oncology patients during the multidisciplinary rounds.…”
Section: Discussionsupporting
confidence: 93%
“…The implementation of the bowel regimen protocol also resulted in a significant increase in the number of BMs for patients in the intervention group, in contrast to the comparison group. This finding is consistent with previous studies that have shown the effectiveness of bowel regimens in improving bowel function (Mozaffari et al, 2018; Zhang et al, 2021). The dynamic role of the case manager in the medical oncology unit helped the nursing and medical teams determine the BM status of oncology patients during the multidisciplinary rounds.…”
Section: Discussionsupporting
confidence: 93%
“…Other aspects would have been interesting as well, e.g., the survival of patients affected by OIC treated or not-treated with PAMORAs like it has been reported for methylnaltrexone in advanced cancer patients [78]. Moreover, between the adverse events, we did not study the abdominal pain evoked by PAMORAs and its relationship with laxation, which has resulted very frequently in some groups of patients [79,80].…”
Section: Limitationsmentioning
confidence: 99%